STRUCTURAL AND COMPOSITIONAL CHARACTERISTICS OF THE OLDEST VOLCANIC GLASS IN THE EARLY PALEOPROTEROZOIC BONINITE-LIKE LAVAS OF SOUTHERN KARELIA - Sharkov E.V.; Trubkin N.V.; Krassivskaya I.S.; Bogatikov O.A.; Mokhov A.V.; Chistyakov A.V.; Evseeva K.A. (My University, 2004)
The oldest volcanic glass in the uniquely fresh siliceous high-Mg (boninite-like) lavas of the Vetrenyi Poyas complex with an age of about 2.41 Ga from the Vetrenyi Poyas rift structure in Karelia was studied for the first time by instrumental methods using a JEM-100C transmission electron microscope with a Kevex-5100 energy-dispersive X-ray spectrometer. Two types of glass were distinguished: (1) basic glass representing portions of initial magmatic melt that had not enough time to crystallize and (2) residual glass occurring in interstices between microspinifex-textured pyroxene and olivine crystals; the latter glass varies in composition from andesite to dacite. It was found that the volcanic glass is composed of amorphous silica containing nanocrystals of hydrous silicates (amphiboles and various phyllosilicates), orthopyroxene, α-quartz, and tridymite and rare grains of halite, anatase, and cuprite. The mineralogical composition of these nanophases is sharply different from the association of phenocrysts and groundmass crystals of the lava, which comprises olivine, aluminous clinopyroxene, plagioclase, and chromite. The nonuniform distribution of nanophases in the glass provides its mottled appearance in back-scattered electron images and variable compositions determined by the electron microprobe. Their distribution is not related to secondary processes but reflects the primary heterogeneity of the melt preserved owing to rapid quenching. The nature of these nanophases is not yet clear. They could be the products of crystallization of partially ordered silicate micelles in a siliceous matrix, which occurred both immediately after glass quenching in a hot material (orthopyroxene, tridymite, and α-quartz) and during subsequent cooling and prolonged evolution in the Earth's crust under much lower temperature conditions, when other nanocrystals were formed.
Keywords: Volcanic Glass; Boninite-Like Lavas; Precambrian::Proterozoic::Paleoproterozoic; Докембрий::Протерозой::Палеопротерозойская